NEW MODES OF HIGH STIR STERILIZATION OF CANNED «COMPOTE CHERRY» USING PRE HEATING OF FRUIT IN BANKS HOT WATER - M. M. Achmedova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Conducted to determine the effect of increasing the temperature of the product prior to sealing the jars for the duration of modes of heat sterilization.It is revealed that the use of pre-heating the fruit in the banks before sealing provides the possibility of increasing the initial temperature of the syrup poured into the banks, increasing the initial temperature of the product, reducing the duration of the cooking process, and therebyimproving the quality of the finished product.